2022
DOI: 10.20473/jaki.v10i2.2022.197-205
|View full text |Cite
|
Sign up to set email alerts
|

Husband's Support in Wife's Anc in Eastern Indonesia: Do Regional Disparities Exist?

Abstract: Background: Previous research has found that husband support can increase the participation of the wife's antenatal care (ANC) to prevent an increase in maternal mortality. Meanwhile, in the eastern region, the effort to provide pregnant women's health services tends to be lower than in Indonesia's other areas. Aims: The study analyzed regional disparities of husbands' support in wives' ANC in eastern Indonesia. Methods: Secondary data from the 2017 Indonesian Demographic and Health Survey were used in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It found that meeting the needs of health services for people with hypertension has not been optimal in Indonesia. In addition, Wulandari et al (2022) reports that there are regional disparities in husbands' support for wives' antenatal care in Eastern Indonesia. Primary infertility women need psychological support in assisting the success of clinical care (Puspitaningrum et al, 2022).…”
mentioning
confidence: 99%
“…It found that meeting the needs of health services for people with hypertension has not been optimal in Indonesia. In addition, Wulandari et al (2022) reports that there are regional disparities in husbands' support for wives' antenatal care in Eastern Indonesia. Primary infertility women need psychological support in assisting the success of clinical care (Puspitaningrum et al, 2022).…”
mentioning
confidence: 99%